Afghanistan's drug career: Evolution from a war economy to a drug economy - Citha Doris Maaß (Stiftung Wissenschaft und Politik (SWP), 2011)
The paper looks into the beginnings and the evolution of drug production in Afghanistan during decades-long war. With 93 per cent of the world production of opiates in 2008 coming from Afghanistan, the country has achieved a monopoly on the illegal world market for opium, morphine and heroin. The starting point for the commercial production of drugs was the anti-Soviet jihad, launched in 1979, which the mujahedeen led with the support of the CIA, the United States and other Western states. Initially, a 'drugs-weapon pipeline' was established, from which a full-scale war economy emerged. After the fall of the Taleban regime in 2001, the US rehabilitated the former mujahedeen leaders who - as the Taleban regime had done - funded themselves to a large extent by trafficking drugs and turned into 'war entrepreneurs'. From 2002 onwards, President Hamid Karzai co-opted these war entrepreneurs into the new political system. As a result, a new drugs economy consolidated, beginning in 2005. The drug economy as a new regulative system in post-war Afghanistan ('criminalized peace') can be characterised as follows: An alliance of interests links the weak Karzai government with the co-opted former warlords; the weak state institutions provide power, sinecure and profits. The illicit economy, based on a drug economy, dominates the rudimentary licit economic sector. The conditions for a stable peace order are unfavourable after the systematic election fraud that marred President Karzai's re-election on 20 August 2009: The power networks of the criminalized peace order are likely to limit President Karzai's room for manoeuvre to carry out drastic reforms. Realistically, it will take 20 to 30 years to weaken the drugs industry and to establish a stable peace order
Keywords: 320